Evidence-based nutritional recommendations for the prevention and treatment of overweight and obesity in adults (FESNAD-SEEDO consensus document): Methodology and executive summary (I/III) Recomendaciones nutricionales basadas en la evidencia para la prevención y el tratamiento del sobrepeso y la obesidad en adultos (consenso FESNAD-SEEDO): Metodología y resumen ejecutivo (I/III) - M. Gargallo Fernández; J. Basulto Marset; I. Breton Lesmes; J. Quiles Izquierdo; X. Formiguera Sala; J. Salas-Salvadó (Nutrición Hospitalaria, 2012)
The present study is a consensus document of two Spanish scientific associations, FESNAD (Spanish Federation of Societies of Nutrition, Food and Dietetics Associations) and SEEDO (Spanish Association for the Study of Obesity), about the role of the diet in the prevention and treatment of overweight and obesity in adults. In this part of the document the methodology and the classification of levels of evidence are described. In order to reach the strongest evidence possible, a systematic review of 543 medical studies dealing with these issues published in the last 15 years (from January 1st 1996 to January 31st 2011) has been conducted. In the executive summary, along with the obtained evidences, a set of degree-classified recommendations are established. These recommendations could constitute a useful tool to design food guides addressed to the nutritional counseling for obesity and overweight treatment. En el presente trabajo se describe la metodología y los grados de evidencia utilizados en la elaboración del documento de consenso de la Federación Española de Sociedades de Nutrición, Alimentación y Dietética (FESNAD) y la Sociedad Española para el Estudio de la Obesidad (SEEDO) sobre el papel de la dieta en la prevención y el tratamiento de la obesidad y el sobrepeso. Para obtener la mayor evidencia posible se ha efectuado una revisión sistemática de los datos de la literatura médica desde el 1 de enero de 1996 al 31 de enero de 2011 (15 años). En el resumen ejecutivo, junto a las evidencias alcanzadas, se establecen unas recomendaciones clasificadas según grados que pueden servir de guía y orientación en el diseño de pautas alimentarias dirigidas a la prevención o al tratamiento de la obesidad o el sobrepeso.